Evaluation of thermal lens fringes using Hilbert and Fourier transform methods - Sarac, Z.; Birkok, H. G.; Taskin, H.; Ozturk, E. (Inst Engineering Technology-Iet, 2011)
This study presents the analysis of thermal lens fringes obtained by heating the Nile-blue/ethanol solution with a He-Cd laser in aMichelson interferometer by utilising the Hilbert transform method (HTM) and the Fourier transform method (FTM) with a Gaussian filter. HTM and FTM are used for obtaining local phase and refractive index change maps of the interferograms. The results reveal that HTM creates harmonics in the frequency spectrum; hence, the signal cannot be filtered very accurately, whereas FTM with a Gaussian filter can create a smooth filtering effect.
Keywords: Liquid Samples